High strain rate properties of materials using compressive split hopkinson pressure bar - Huang, Hua (2016)
There is strong demand for materials such as aluminum alloys and magnesium alloys which have great material properties and high cost-performance ratio making them favorable for applications in automotive industry and other industries. And to understand the material behavior under high strain rate conditions, the compressive Split Hopkinson Pressure bar technique which is one of the most common ways is used due to its reliability and accuracy after various calibrations. Before experiments, equipment such as pressure bars, strain meter & photodiodes must be set up and calibrated properly. To further enhance accuracy, specimens must be machined and polished with highly precise dimensions. During the compressive experiment, Strain gauges detect the impact and send the strain signals which are received by oscilloscope and converted into data using Excel for analysis of stress, strain and strain rate. After empty run tests, key parameters such as wave velocity, impact velocity and average strain rate were analysed. Comparison with past researches, repeatability tests and other calibrations were done to ensure accuracy with Al6061-T6 being used as calibration material for its material properties being most well-known. Next, AM50 and AZ91D which are magnesium alloys were investigated to find out their dynamic material properties such as relationship between stress and strain, relationship between strain rate and time at varying pressure and varying insertion distance respectively. With data found, relationships among insertion distance, pressure, impact velocity and average strain rate can be established and it can be used to forecast on impact velocity and average strain rate given insertion distance and pressure.